Palliative surgical treatment for cutaneous metastatic tumor is a valid option for improvement of quality of life. Issue 1 (16th June 2015) - Goto, Hiroyuki; Omodaka, Toshikazu; Yanagisawa, Hiroto; Yoshikawa, Shusuke; Yoshida, Yuichi; Yamamoto, Osamu; Kiyohara, Yoshio
Abstract: A cutaneous metastatic tumor is relatively rare, and patients with such a tumor usually have a poor prognosis. Even if the metastases can be treated, the treatment cannot improve the prognosis. However, neglecting metastatic lesions sometimes results in a great deterioration of quality of life. Cutaneous metastatic foci are generally treated with chemotherapy and/or radiotherapy. On the other hand, surgical treatment is sometimes chosen for cutaneous metastases. In this study, we analyzed data for 40 patients with cutaneous metastatic tumors who received surgical treatment at Shizuoka Cancer Center between January 2009 and August 2014. Among these cases, lung cancer was the most common primary cancer and the craniocervical region was the most frequent metastatic site. Among the patients who died, the average duration to death after the operation was 186 days. We consider that resection of cutaneous metastatic tumors as palliative therapy is an appropriate therapeutic option if the patient's condition permits resection. Such treatment can improve quality of life for both the patients and their families.